Optimizing boron application methods and dosages to enhance jute (Corchorus olitorius) seed yield and quality under sub-tropical climate - Tapan Kumar; Pritthee Mallick Tama; Syed Aflatun Kabir Hemel; Ranjit Kumar Ghosh; Md Imran Ali; Abdullah Al-Bakky; Abdul Alim (Heliyon)
Bangladesh, despite being a top raw jute producer, struggles with inadequate jute seed quantity and quality due to some unforeseen circumstances. Boron is a key micronutrient for enhancing crop seed yield and quality. However, research on its effects on jute (Corchorus olitorius) seed production in Bangladesh remains limited, highlighting a significant knowledge gap. Therefore, a two-year field study was conducted at the Bangladesh Jute Research Institute, Regional Station in Faridpur to examine the effects of various boron application methods and doses on Corchorus olitorius seed production. The experiment included ten treatments combining three boron doses (2.0, 3.0, and 4.0 kg/ha) with three different application methods: (1) full dose as basal application, (2) full dose as foliar spray in two equal split and (3) haft the dose as basal application with the remaining half as foliar spray in two equal splits. An additional treatment without boron served as the control. The experiment, using the jute variety BJRI Tossa Pat 8, was conducted in a randomized complete block design to account for environmental variability and enhance treatment comparison. The study revealed that, independent of application methods and doses, boron application significantly improved seed yield and germination percentage compared to treatments without boron. Foliar application of boron at 3.0 kg/ha significantly enhanced yield contributing characters, including the number of capsules/plant, capsule length, and 1000-seed weights, compared to control and basal treatments. Additionally, boron application consistently improved seed yield and germination percentage across all methods and doses. The 3.0 kg/ha foliar treatment, applied half at 20–25 days after sowing and the remainder at the first flowering stage, yielded the highest results for Corchorus olitorius. Principal component analysis indicated that the number of seeds per capsule, capsule length, and seed yield were the main contributors. So, 3.0 kg/ha foliar boron treatment, applied half at 20–25 days after sowing and the remainder at the first flowering stage is recommended for late jute seed production to achieve optimum seed yield and net profit.